'Of Mice and Dementia': A filmed conversation on the use of animals in dementia research. (November 2018) - Tamagnini, Francesco; Cotton, Mark; Goodall, Olwen; Harrison, Gillian; Jeynes, Charlie; Palombo, Francesca; Tomkow, Jean; Tomkow, Terry; Wedgwood, Kyle; Welsman, Jo
Preclinical science research focuses on the study of physiological systems regulating body functions, and how they are dysregulated in disease, in a non-human setting. For example, cells in a dish, computer simulations or animals. Scientific procedures traditionally involve a specialist scientist developing a hypothesis and subsequently testing it using an experimental set-up. The results are then disseminated to the wider scientific community, following peer review and only at the last stage the news will reach the general, lay public. In the last few years, some research funding institutions have promoted a different model, with the direct involvement of members of the public in the research co-creation, from the hypothesis development, to the grant revision, project monitoring and results communication. We personally experienced this model and brought it to a further level by producing a movie. Animal research is a very controversial topic as, while still being necessary for the investigation of body functions, it brings about issues related to the ethics, the regulation and the practical execution of experimental procedures on animals. Here we discuss the different stages of the ideation, production and outcomes of the movie 'Of Mice and Dementia', a filmed conversation on animal experimentation in dementia research. The conversation was between scientists and lay people with a direct experience of dementia.